Effects of lithium coating of the chamber wall on the STOR-M tokamak discharges. (5th June 2019) - Rohollahi, A.; Elgriw, S.; Mossman, A.; Adegun, J.; Bsharat, H.; Voldiner, I.; Xiao, C.
Abstract: Lithium (Li) coating of the inner wall of tokamaks has been considered a practical technique to reduce fuel recycling. Li-coating also improves the tokamak wall condition and reduces high- Z material release from the tokamak wall during discharges. In a recent campaign in the STOR-M tokamak ( R / a   =  0.46/0.12 m, B t   =  0.7 T, I p   =  25 kA), 100 mg of Li has been coated on the tokamak chamber using a physical vacuum evaporation applicator developed by General Fusion Inc. A reduction in the plasma impurity contents and increase in both the peak plasma current and duration have been observed after Li-coating. The line averaged electron density in the plasma reduced after Li-coating. An increase in hard x-ray radiation has also been observed, suggesting an enhanced production of suprathermal run-away electrons because of the reduced electron density. In addition the Li atom emission line has been used to measure the plasma flow velocity based on the Doppler shift of the emission.